Life-Threatening Hemorrhage During Patent Ductus Arteriosus Ligation in a Cat: Xenotransfusion With Canine Blood - Dupont, Julien; Serteyn, Didier; Sandersen, Charlotte (Frontiers in Veterinary Science, 2020)
A 13-month-old Sphynx cat was referred for patent ductus arteriosus (PDA) ligation. A left thoracotomy was performed and the PDA was efficiently ligated. Immediately after chest tube placement, it presented extensive intrathoracic bleeding from the caudal intercostal artery. In view of the absolute necessity of a blood transfusion and given that compatible feline blood was not available, xenotransfusion of canine blood was administered to the cat and resulted in a positive outcome.